2022
DOI: 10.1021/acs.chemmater.2c00684
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Hydrothermal Synthesis of Mesoporous First-Row Transition Metal Ferrites

Abstract: Nanocrystalline and monomodal pore size mesoporous transition metal oxides have attracted considerable attention because of their interconnected networks and high surface areas. These materials have demonstrated improved characteristics such as electron transport, dye loading, electrolyte permeation, and oxidative capabilities when compared to those of typical nanostructured catalysts when used for different catalytic applications. Of particular interest are ferrites that have demonstrated roles in biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(96 reference statements)
2
3
0
Order By: Relevance
“…The two A 1g phonon mode were observed at 225 and 494 cm –1 , while three E g phonon modes correlate to the peaks at 298, 412, and 609.4 cm –1 . The other two peaks of E g are missing; this could be associated with the lower intensity as described by Achola et al These findings confirm that there could be a mixture of magnetite and hematite. Similar results of Fe 2 O 3 nanoparticles have also been shown by Marshall et al…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The two A 1g phonon mode were observed at 225 and 494 cm –1 , while three E g phonon modes correlate to the peaks at 298, 412, and 609.4 cm –1 . The other two peaks of E g are missing; this could be associated with the lower intensity as described by Achola et al These findings confirm that there could be a mixture of magnetite and hematite. Similar results of Fe 2 O 3 nanoparticles have also been shown by Marshall et al…”
Section: Resultssupporting
confidence: 89%
“…The Raman spectrum at 298, 412, and 609.4 cm −1 . The other two peaks of E g are missing; this could be associated with the lower intensity as described by Achola et al 64 These findings confirm that there could be a mixture of magnetite and hematite. Similar results of Fe 2 O 3 nanoparticles have also been shown by Marshall et al 65 TGA was conducted to understand the thermal stability, decomposition temperature, and decomposition rate of the prepared nanoparticles.…”
Section: ■ Materials and Methodssupporting
confidence: 83%
“…The optimized nanosheets thus formed have proven to be effective OER catalyst with a greater stability (62 h) and an overpotential of 268 mV at 10 mA cm −2 . On a similar note, NiFe 2 O 4 synthesized using microwave assisted hydrothermal synthesis by Suib (Achola et al, 2022) has shown low overpotential of 278 mV at 10 mA cm −2 as an OER catalyst.…”
Section: Tmos As Photocatalystsmentioning
confidence: 87%
“…The seminal work on mesoporous materials by Mobil Corporation (Kresge et al, 1992) pioneered extensive research in the synthesis and utilization of porous TMOs. Nano-size mixed valent mesoporous oxides have received much attention in catalysis, electrochemistry, and adsorption due to their high surface areas and improved mass transfer within pores (Wang et al, 2017;Achola et al, 2022). Our lab has done considerable research on synthesizing mesoporous TMOs in recent years (Dang et al, 2021;Achola et al, 2022;Zhao et al, 2022a;Tabassum et al, 2022).…”
Section: Synthesis and Characterization Of Tmosmentioning
confidence: 99%
“…Among porous materials, mesoporous materials have fascinated researchers due to their enormous applications in catalysis, adsorption, electrochemistry, gas sensing, energy conversion and storage, and photochemistry. To synthesize mesoporous materials, usually two types of templates (hard and soft) are utilized via different synthesis processes/methods. Some of the common synthesis process/methods are sol–gel, single-micelle-directed, inverse micelle, nanocasting, alignment and grafting, electrochemical, and the metal dissolution .…”
Section: Introductionmentioning
confidence: 99%